Study of Proportional Variation of Geopolymer Concrete which Self Compacting Concrete - Purwanto P.; Himawan Indarto (Universitas Islam Sultan Agung, 2019)
Portland cement production process which is the conventional concrete constituent materials always has an impact on producing carbon dioxide (CO2) which will damage the environment. To maintain the continuity of development, while maintaining the environment, Portland cement substitution can be made with more environmentally friendly materials, namely fly ash. The substitution of fly ash material in concrete is known as geopolymer concrete. Fly ash is one of the industrial waste materials that can be used as geopolymer material. Fly ash is mineral residue in fine grains produced from coal combustion which is mashed at power plant power plant [15]. Many cement factories have used fly ash as mixture in cement, namely Portland Pozzolan Cement. Because fly ash contains SiO2, Al2O3, P2O3, and Fe2O3 which are quite high, so fly ash is considered capable of replacing cement completely.This study aims to obtain geopolymer concrete which has the best workability so that it is easy to work on (Workable Geopolymer Concrete / Self Compacting Geopolymer Concrete) and obtain the basic characteristics of geopolymer concrete material in the form of good workability and compressive strength. In this study, geopolymer concrete is composed of coarse aggregate, fine aggregate, fly ash type F, and activators in the form of NaOH and Na2SiO3 Be52. In making geopolymer concrete, additional ingredients such as superplastizer are added to increase the workability of geopolymer concrete. From this research, the results of concrete compressive strength above fc' 25 MPa and horizontal slump values reached 60 to 80 centimeters.